Effects of introducing balanced rations on greenhouse gas emissions from small scale Indonesian dairy farms - Vries, Marion de; Sadana, Edi; Suharyono, Deni; Wouters, Bram; Apdini, Titis (2019)
Poster by Marion de Vries presented at the 5th Global Science Conference on Climate-Smart Agriculture in Bali in October 2019.